(untitled) (SCIENCE TIME JOURNAL, 2026)
This article explores the theoretical foundations of inclusive education and provides a scientific analysis of the concept of special educational needs. It examines the psychological, cognitive, and communicative characteristics of learners with special educational needs, identifying their specific requirements in the educational process. The study also investigates effective inclusive language teaching strategies for such learners, including differentiated instruction, individualized learning pathways, and the use of adapted teaching materials. Furthermore, the article highlights the importance of collaborative learning in developing students’ language skills within an inclusive educational environment and justifies its effectiveness with practical examples. The findings of the study contribute to improving inclusive education practices and enhancing the effective engagement of learners with special educational needs in language learning.